(untitled) (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan, 2018)
Effect of cage construction and stocking densites on the growth, production and feed conversion was evaluated for catfish (Pangasius djambal) for 6 months experimental period. Fingerlings with initial mean weight of 31,53 gram were reared in rectangular and circle pen at density of 50, 75 And 100 fish/pen/m3. The fingerlings were fed on commercial feed containing 27% protein at 3% of body weight a day. The result showed that interaction effect of pen shape and stocking density on fish growth, production, survival rate and feed conversion was not significant difference (P>0,05). Stocking densities difference were significant effect on growth and production. Low stocking density resulted fast growth, edlow production and high stocking density result slow growth and hight production. Growth ranging from 369,99-430,64 g, production 58.970-91.050 g, survival rate 75-88% and feed conversion 2,71-2,85. Keywords: Pangasius djambal, pen culture, density